Revision of the Ethiopian Essential Health Service Package: An Explication of the Process and Methods Used - Getachew Teshome Eregata; Alemayehu Hailu; Zelalem Adugna Geletu; Solomon Tessema Memirie; Kjell Arne Johansson; Karin Stenberg; Melanie Y. Bertram; Amir Aman; Ole Frithjof Norheim (Taylor & Francis Group, 2020)
To make progress toward universal health coverage, countries should define the type and mix of health services that respond to their populations' needs. Ethiopia revised its essential health services package (EHSP) in 2019. This paper describes the process, methodology and key features of the new EHSP. A total of 35 consultative workshops were convened with experts and the public to define the scope of the revision, develop a list of health interventions, agree on the prioritization criteria, gather evidence and compare health interventions. Seven prioritization criteria were employed: disease burden, cost effectiveness, equity, financial risk protection, budget impact, public acceptability and political acceptability. In the first phase, 1,749 interventions were identified, including existing and new interventions, which were regrouped and reorganized to identify 1,442 interventions as relevant. The second phase removed interventions that did not match the burden of disease or were not relevant in the Ethiopian setting, reducing the number of interventions to 1,018. These were evaluated further and ranked by the other criteria. Finally, 594 interventions were classified as high priority (58%), 213 as medium priorities (21%) and 211 as low priority interventions (21%). The current policy is to provide 570 interventions (56%) free of charge while guaranteeing the availability of the remaining services with cost-sharing (38%) and cost-recovery (6%) mechanisms in place. In conclusion, the revision of Ethiopia's EHSP followed a participatory, inclusive and evidence-based prioritization process. The interventions included in the EHSP were comprehensive and were assigned to health care delivery platforms and linked to financing mechanisms.